PENERAPAN FUNGSI MANAJEMEN KELOMPOK TANI DALAM AGRIBISNIS PADI SAWAH DI DISTRIK AIMAS KABUPATEN SORONG - R. Silehu; E Y. Arvianti (Universitas Tribhuwana Tunggadewi, 2012)
An effort has been and is being carried out by the government to increase rice production and farmers while increasing revenue in the District Aimas, as the largest rice producer in the district of Sorong, is to adopt a management function in farmer groups to improve the application of rice agribusiness. The purpose of this study to (a) Determine the influence of some management functions are implemented by farmers on the application of agri Aimas paddy in the district, Sorong regency, (b) Knowing and learning costs, revenues, benefits and feasibility of rice agribusiness Aimas District, District Sorong, (c) Knowing the factors that influence the production of rice production in the District Aimas, Sorong regency, as efforts to improve the efficient use of production factors, and (d) Determine the efficiency of rice agribusiness production factors. The results showed that the application by farmers of management functions simultaneously and significantly affect the application of partial agribusiness Aimas paddy in the district, Sorong regency.Application of management functions to contribute 66% of the variation in the application of rice agribusiness Aimas district, Sorong regency. Seen partially, a function that significantly affect the application of rice agribusiness adan planning and evaluation functions. Agribusiness rice worth it in terms of RCR value 5.53, which means that any additional production cost of Rp. 1, - will generate revenue of Rp. 5:53,-. Production factors of labor, seed, fertilizer urea, KCl fertilizer, fertilizer and pesticides SP36 simultaneously significantly affect rice production. Variations of factors of production contributed 65.8% of the variation in rice production. The dominant factor affecting rice production is labor and seed. The use of production factors of labor, seed, fertilizer and pesticides KCl inefficient and needs to be reduced its use, while. The use of urea fertilizer production factors and SP36 and yet efficient and necessary, its use to increase production